The effect of the cooperative integrated reading and composition (CIRC) learning model on learning motivation and reading comprehension ability of upper-grade students at SD Negeri 14 Batarang - Wahyuni Wahyuni; Yusmah Yusmah; Muhammad Hanafi (Universitas Muhammadiyah Enrekang, 2025)
This research is a quantitative study. The population and sample in this research consisted of all upper-grade students, totaling 30 students. The data collection techniques used were tests, observations, and documentation. The data analysis techniques included descriptive analysis, Paired Sample t-Test, Homogeneity Test, and Independent Sample t-Test using IBM SPSS Statistics software.The purpose of this research was to determine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving students’ learning motivation and reading comprehension ability at the elementary school level. The study employed a quantitative approach with a quasi-experimental design, involving an experimental class taught using the Cooperative Integrated Reading and Composition (CIRC) model and a control class taught using conventional methods. The data were analyzed using descriptive statistics, frequency distribution, homogeneity test, Paired Sample t-Test, and Independent Sample t-Test. The results of the study revealed that the Cooperative Integrated Reading and Composition (CIRC) learning model was significantly more effective in increasing students’ learning motivation compared to conventional learning. The average motivation score of students in the experimental class increased from 68.47 to 89.73, while in the control class it only increased from 60.67 to 67.40. Moreover, the evenness of results was better indicated by the decrease in standard deviation, and the statistical tests showed a significant difference (Sig. < 0.05).In terms of reading comprehension ability, the findings also demonstrated significant effectiveness. The average score of the experimental class increased from 67.53 to 92.00, whereas the control class only increased from 64.53 to 77.53. A total of 94% of students in the experimental class achieved the “Excellent” category, while none in the control class reached this level. The t-test results also indicated a significant difference (Sig. < 0.05), with homogeneous variance ensuring valid comparison.Therefore, it can be concluded that the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model is effective in enhancing elementary school students’ learning motivation and reading comprehension ability in an optimal and equitable manner.